Answer:
The correct options are;
B) 3x + 4 – 3 – x
D) 2x + 1
E) 2x + 4 – 3
Explanation:
Which expressions can you form by rearranging x+x+x+1+1+1+1+(-1)+(-1)+(-1)+(-x) Check all that apply.
A) x – x + 2x – 2 + 4
B) 3x + 4 – 3 – x
C) 4x + 1
D) 2x + 1
E) 2x + 4 – 3
x+x+x+1+1+1+1+(-1)+(-1)+(-1)+(-x)
positive sign multiply by negative sign will give a negative sign, hence;
x+x+x+1+1+1+1-1-1-1-x
Rearranging the equation;
x + x + x -x+ 1+1+1+1 -1-1-1
=3x -x + 4 -3
=2x + 1
We can also re-arrange it to give 3x + 4 - 3 -x
because
3x + 4 -3 -x
=3x -x + 4 -3
=2x + 1
Also, we can re-arrange it to give 2x + 4 - 3
since 2x + 4 - 3 = 2x + 1
The correct options are;
B) 3x + 4 – 3 – x
D) 2x + 1
E) 2x + 4 – 3